ECONOMIC ASSESSMENT OF RECREATIONAL AND TOURIST RESOURCES OF KHMELNITSKY REGION IN NEW CONDITIONS OF MANAGEMENT (Development Service Industry Management, 2023)
Khmelnytskyi region belongs to those regions of Ukraine with the most favorable natural and ecological conditions, a significant number of historical and cultural objects, which are the basis for the development of the recreational complex. This complex includes industries involved in the organization of public recreation: tourism, sanatorium-resort economy. Recreational resources in particular, as well as the natural tourism potential of the territory as a whole are calculated as a result of the overall economic assessment of the potential of certain types of natural resources of the Khmelnytskyi region. The component structure of the integrated PTP reflects the intra-species and inter-species relations of natural resources that have developed in the region as a result of the development of the natural process and the action of socio-economic factors. When using the resource and recreational potential of the territory, a certain recreational and ecological effect is achieved. By the recreational effect from the use of resource-recreational potential, we understand the obtained results of the qualitative impact (medical and recreational, sports, cognitive, entertainment effects) of recreational resources on vacationers, as well as the actual volumes of resource use. The ecological effect reflects those changes in resources that have occurred as a result of their recreational use. Therefore, the efficiency of using the resource-recreational potential of the territory will be determined by the ratio of the actually received recreational and potential effects, as well as the ratio of the changes noted in the resources during their exploitation and the maximum permissible ones.In the article the state and efficiency of the use of recreational and tourist resources of Khmelnitsky region in new conditions of management are considered. The indicators of economic performance of natural and tourist potential and levels of provision of Khmelnitsky region population with them are analyzed and determined. Modern structure of natural and tourist potential of the region is substantiated and spatial analysis of quantitative and qualitative indicators per a person is made. In the paper the value of integral natural and resource potential of Khmelnitsky region and administrative areas and also territorial structure of integrated natural and resource potential are determined. The state of recreational resources of Khmelnitsky region is analyzed and prospects of their efficient use are substantiated.
Keywords: recreational resources; recreational and tourist potential; environmental management; integrated natural resources; territorial structure; tourism industry